Efeito do aquecimento dos pés sobre a sensibilidade tátil dos pés e controle postural de idosos com obesidade - Machado, Mathias Sosa (2025)
Standing posture relies on the integration of sensory information and is essential for promoting independence in older adults. However, aging is associated with deficits in the sensory-motor system, increasing the risk of falls in this population. One such deficit is the reduction in foot tactile sensitivity, which may be exacerbated by obesity. Interventions that enhance tactile sensitivity, such as warming the skin of the feet, may positively influence postural control. This study investigated whether foot warming improves tactile sensitivity and postural control in young adults, older adults, and obese older adults. The results indicate that obese older adults benefit the most from this intervention, showing improvements in tactile sensitivity and postural stability.